Sky (Symphony in the Flint Hills, 2014)
“Prairies lead into the sky!” The remarkable sky of the Flint Hills seldom fails to create awe and encourage reflection in the beholder. Throughout the years artists have interpreted the prairie sky in many ways, but it is not only the sky that serves as Prairie Muse for the arts, as is seen in the stories and poems found in this section of the Field Journal.
Keywords: sky; Flint Hills; day; night; stars; clouds; Prairies; native; Kansas